2003
DOI: 10.1016/s1201-9712(03)90054-3
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of influenza vaccine effectiveness among Malaysian pilgrims attending the Haj in Saudi Arabia

Abstract: Influenza vaccine was effective in preventing clinic visits for influenza-like illness and antibiotic use. Pilgrims traveling to the Haj in Saudi Arabia should consider influenza vaccination use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 9 publications
0
32
0
Order By: Relevance
“…Similarly, transmission among pilgrims may increase through interaction with local residents. Finally, widespread antibiotic use during the Hajj [17,18] may select for resistant clones that are more likely to persist in carriage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, transmission among pilgrims may increase through interaction with local residents. Finally, widespread antibiotic use during the Hajj [17,18] may select for resistant clones that are more likely to persist in carriage.…”
Section: Discussionmentioning
confidence: 99%
“…While substantial work has been performed on transmission during the Hajj of Neisseria meningitidis group A [14][15][16], influenza [17][18][19] and respiratory diseases as a whole [20][21][22], limited data are available for pneumococcal disease. In addition, although the dominant invasive pneumococcal serotypes in KSA among adults and children are 4, 3, 19F, 9V, 6A, 19A, 14 and 23F (accounting for 75% of all serotypes) [23], the current serotype distribution among Hajj pilgrims is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 17 studies reported on influenza vaccine uptake [9,[11][12][13]15,[17][18][19][20][26][27][28]35,45,[47][48][49], with the remaining 17 studies additionally assessing influenza vaccine effectiveness [10,14,16,[21][22][23][24][25][29][30][31][32][33][34]36,44,46].…”
Section: Influenza Vaccinementioning
confidence: 99%
“…In this review, we summarize the available literature on the transmission of antibiotic resistance during the Hajj and suggest possible solutions. of antibiotic resistance during the Hajj is over-use of antibiotics [6,7]. In a cohort of 820 pilgrims, 84% received antibiotics for upper respiratory tract infection [7].…”
Section: Introductionmentioning
confidence: 99%
“…of antibiotic resistance during the Hajj is over-use of antibiotics [6,7]. In a cohort of 820 pilgrims, 84% received antibiotics for upper respiratory tract infection [7]. In another study of 2070 Pakistani pilgrims, 17% had received antibiotics [6].…”
Section: Introductionmentioning
confidence: 99%